Credit Accessibility and Growth of Small and Medium Enterprises in Bujumbura, Burundi - Delphin, Bariko; Awolusi, Olawumi Dele (Journal of Economics and Behavioral Studies, 2023)
The purpose of this study was to investigate the effect of credit accessibility on the growth of small and medium enterprises in Bujumbura, Burundi. The study was guided by the following objectives: i) to determine the effect of creditworthiness to credit accessibility on the growth of SMEs in Bujumbura; ii) to establish the effect of business characteristics to credit accessibility on the growth of SMEs in Bujumbura, and iii) to examine the effect of information available to credit accessibility on the growth of SMEs in Bujumbura. The study employed a descriptive survey research design. The target population was 347 and the sample size determined using the Slovenes formula was 186, but 167 respondents participated successfully in the study. The research instrument was a questionnaire and data were analyzed using frequency and percentage tables, mean and standard deviations, and linear and multiple regression analyses. The study found that creditworthiness to access credit had a significant effect on the growth of SMEs (Adjusted R2=0.059, p=0.001). In addition, the study revealed that business characteristics to access credit had a significant effect on the growth of SMEs (Adjusted R2=0.242, p=0.000). Furthermore, the study revealed that information available to access credit had a significant effect on the growth of SMEs (Adjusted R2=0.116, p=0.000). The study concluded that credit accessibility significantly affects the growth of SMEs. Thus, the study recommended that the owners of SMEs should strive to ensure that they have collateral security and proper documentation before they seek credit from financial institutions, SMEs should also form and register an association that is recognizable by law in Burundi. Likewise, the owners of SMEs should seek the support of professional auditors to audit their books of accounts at least every year.